I Improving Student Learning Outcomes of Class VII.A Middle School 5 Kendari in Indonesian Subjects Through the Student Learning Achievement Division (STAD) Cooperative Learning Strategy (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2020)
The purpose of this study was to improve the learning outcomes of class VII A students of SMP Negeri 5 Kendari in Indonesian through cooperative learning strategy student team achievement division (STAD). The implementation of this classroom action research uses the following procedures: (a) planning; (b) implementation; (c) observation; (d) reflection. With increasing student learning outcomes and teacher skills in managing learning. The results of this study indicate that student learning outcomes can increase before implementing the STAD cooperative learning strategy than after using the strategy. The learning result shows that the class average which was originally 73.28 in the preliminary activity stage, increased to 80.03 in the first cycle, and then increased to 87.93 in the second cycle. Classical completeness increased from 40% in the preliminary activity stage, to 72.5% in cycle I, and to 97.5% in cycle II. Likewise, student activity increased from 17.5% in the preliminary activity stage, to 47.5% in cycle I, and to 82.5 in cycle II. Thus the STAD cooperative learning strategy can improve the learning outcomes of grade VII A students of SMP Negeri 5 Kendari.